PENGARUH KOMPETENSI DAN MODAL SOSIAL TERHADAP KINERJA DIMEDIASI KOMITMEN ORGANISASIONAL ( STUDI PADA GURU SMP NEGERI DI KABUPATEN PATI ) - Suharto, Edy (Students Journal of Economic and Management, 2012)
This study aimed to: examine the effect of variable competence of teachers and social capital on the performance of the teacher in junior high organizational commitment mediated. The usefulness of this study to clarify and extend previous research on the influence of competence and social capital on the performance of teachers organizational commitment to mediation. This research is the research field. using a quantitative approach. The population in this study were all in junior high school teacher Pati, totaling 426 people. Samples were taken using the technique in a proportional number of Slovin 206 teachers. Techniques of data analysis starts from the test instrument, the classical assumption test, the test model, multiple linear regression analysis, hypothesis testing using t-test and test the mediating effect (path analysis). The results showed that: (1) the teachers competence has positive effect and significant on organizational commitment in the junior high school Pati, (2) Social capital has positive effect but not significant on organizational commitment in the junior high school Pati, (3) teacher competence has positive effect and significant on teachers performance in the the junior high school Pati, (4) Social capital has negative effect and no significant on teacher performance in the junior higj schools Pati, (5) organizational commitment has a positive effect and significant on teachers performance in the junior school Pati, (6) organizational commitment does not mediate of teacher competence on teacher performance in the junior high school Pati. The influence of teacher competence on teacher performance are more effective (direct), and (7) Organizational commitment school does not mediate of social capital on theacher performance in the junior high school Pati. The influence of social capital on teacher performance are more effective (direct). Â  Keywords : Â teacher competence, social capital, teacher performance, and commitment organizational